Sensitivity to Phosphonoacetic Acid: A New Phenotype to Probe DNA Polymerase δ in Saccharomyces cerevisiae - Li, Lei (Genetics Society of America, 2005)
A mutant allele (pol3-L612M) of the DNA polymerase δ gene in Saccharomyces cerevisiae that confers sensitivity to the antiviral drug phosphonoacetic acid (PAA) was constructed. We report that PAA-sensitivity tagging DNA polymerases is a useful method for selectively and reversibly inhibiting one type of DNA polymerase. Our initial studies reveal that replication by the L612M-DNA pol δ requires Rad27 flap endonuclease activity since the pol3-L612M strain is not viable in the absence of RAD27 function. The L612M-DNA pol δ also strongly depends on mismatch repair (MMR). Reduced viability is observed in the absence of any of the core MMR proteins—Msh2, Mlh1, or Pms1—and severe sensitivity to PAA is observed in the absence of the core proteins Msh6 or Exo1, but not Msh3. We propose that pol3-L612M cells need the Rad27 flap endonuclease and MMR complexes composed of Msh2/Msh6, Mlh1/Pms1, and Exo1 for correct processing of Okazaki fragments.